HPLC-MS/MS coupled with equilibrium dialysis method for quantification of free drug concentration of pazopanib in plasma. Issue 4 (April 2020) - Toh, Yi Long; Pang, Yi Yun; Shwe, Maung; Kanesvaran, Ravindran; Toh, Chee Keong; Chan, Alexandre; Ho, Han Kiat
Abstract: Background: The selective occurrence of hepatotoxicity observed with use of pazopanib may be attributed to its high level of plasma protein binding and low hepatic extraction ratio. The primary objective was to investigate changes in free drug concentration amongst patients with varying albumin concentrations. Methods: A HPLC-MS/MS method using C18 column (4.6 × 150 mm, 5 μm) with ESI source in positive mode had been developed and validated for the quantitative determination of free pazaopanib concentration in human plasma. Prior to sample preparation, patient samples were subjected to 6-hour equilibrium dialysis with molecular weight cut-off set at 8000 Da. Results: The calibration curves were linear over the range of 5–1000 ng/mL, with a lower limit of quantification of 5 ng/mL. The intra-day and inter-day precisions and accuracies were all within ± 15 %, at 3 different quality controls. Higher median fraction unbound of pazopanib were observed in patients (n = 17) with lower than normal albumin concentrations. Conclusion: With the developed assay, monitoring of plasma free concentrations may be evaluated as an indicator of pazopanib exposure in patients. Abstract : Pazopanib; Plasma free drug concentration; Fraction unbound; Liquid chromatography-tandem mass spectrometry; Equilibrium dialysis; Pharmacology; Clinical toxicology; Oncology; Evidence-based medicine; Clinical research.